MOTIVATION FOR THE PERFORMANCE OF PRIVATE TEACHERS IN BANG PHLAT DISTRICT, BANGKOK - Chantratree, Rattikan; Chaowarakul, Jitiyaporn; Mecharoen, Salinee (Journal of Educational Review Faculty of Education in MCU, 2024)
The purposes of this research is a mixed method. The research objectives were to: 1) Studying the motivation for the performance of private teachers in Bang Phlat District, Bangkok. 2) Compare the work motivation of private teachers in Bang Phlat District, Bangkok, classified by gender, age, average monthly income, status, educational level, and work experience. and 3) Study methods for enhancing motivation in the work of private teachers in Bang Phlat District, Bangkok. The research is divided into 2 parts. Part 1 is quantitative research. The research samples were 201 private teachers. The instrument for data collection was a set of questionnaires and the statistics for data analysis were mean, standard deviation, t–test (Independent Samples), and F–test (One –way ANOVA). Part 2 is qualitative research. The research samples were 5 educational institution administrators. The instrument for data collection was a set of structured interviews, and data analysis used content analysis. The results of the research showed that: 1) The motivation in the performance of private teachers in Bang Phlat District, Bangkok overall, is at a high level. When considering each aspect, it was found to be at the highest level. In order from highest lowest, the first are: Responsibility Work success and work characteristics are at a high level in order from highest to lowest. The first is acceptance and respect. Opportunity for growth and progress, respectively. 2) The results of the hypothesis testing found that Private teachers with gender, age, status, education level, and work experience There is motivation in the work of private teachers in Bang Phlat District, Bangkok. no different. As for the average monthly income, they are different with statistical significance at the 0.05 level and 3) Guidelines for enhancing motivation in private teachers’ work include: Supporting teachers to continue their education Promoting teachers to work as a team Promoting advancement in the teaching profession Clearly defining the scope of work, practicing leadership, and providing morale and encouragement.